NILAI SUFISTIK DALAM SURAH AL-WAQI’AH : (Kajian Tafsir Tematik) - Mutma’innah, Afifatul; Shohib, Muhammad (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2023)
Starting from the phenomenon of consistency in reading surah al-waqiah carried out by various circles of society, making this surah look special especially with the rich virtues that accompany it. Therefore, this consistency needs to be controlled by the appreciation of the meaning of the verse through the inner Interpretation from which Sufistic value can be found. The orientation referred to in the filtering of Sufistic values is to overcome mental problems that often forget the essence of the life of the soul. Sufistic values will add value in matters of worship. This research is a literature review research conducted with a qualitative approach and uses thematic interpretation methods by collecting verses according to the topic to be studied. The thematic method focuses on only one theme from the themes scattered in the Qur'an with the results of the study of verses that have Sufistic value based on the cues captured by a Sufi. These verses are verses 1 and 2, 59-62, 71-73, 75, 79, and 85. The result obtained from the interpretation of verses containing Sufistic value, namely status 1. al-Faqîr, i.e. needing Allah, made him have to make an effort 2. Tazkiyyah al-Nafsiyah (purifying the soul). Order 3. Yaqin, planted firmly in his heart until he reached the 4th position. Fana', where a person is only aware of God's presence within him. Keywords: Sufistic values, Surah al-Wãqi'ah, Thematic.